DARI CARUT MARUT PENEGAKAN HUKUM DI LAUT MENUJU PENEGAKAN HUKUM YANG PROGRESIF - Anwar, Khaidir (PRAEVIA)
The study investigated the oferlap of authority in the managemen of the sea. research using normative judical approach. the result showd that need to be estabilished maritime law as "legal umbrela" in managing the marine waters of indonesia. formation of legislation on water management must accommodate legal ideals of lifing in society and legal culture. therefore, the law must be humane, so that awareness of the law will reach the stage where internalization was born confidence in the purpose of the rules in question, regarrdless of influence or values of the group or the holders of power and control.